2011
DOI: 10.1074/jbc.m110.163295
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia H1-related Phosphatase Is a Phosphatase of ErbB Receptors and Is Down-regulated in Non-small Cell Lung Cancer

Abstract: Vaccinia H1-related phosphatase (VHR) is classified as a dual specificity phosphatase. Unlike typical dual specificity phosphatases, VHR lacks the MAPK-binding domain and shows poor activity against MAPKs. We found that EGF receptor (EGFR) was a direct substrate of VHR and that overexpression of VHR down-regulated EGFR phosphorylation, particularly at Tyr-992 residue. Expression of VHR inhibited the activation of phospholipase C␥ and protein kinase C, both downstream effectors of Tyr-992 phosphorylation of EGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 33 publications
3
68
0
Order By: Relevance
“…We also demonstrated that low DUSP3 levels had a significant correlation with high KDM2A levels and often occurred in NSCLC tumors. In line with our results, it has been shown that DUSP3 is downregulated in NSCLC and that DUSP3 overexpression leads to decreased cell proliferation and reduced tumor growth in a xenograft mouse model (24). Together with this Stably KDM2A-depleted (shKDM2A#1 and shKDM2A#2) cells and control cells (shControl) were subcutaneously implanted into mice.…”
Section: Tablesupporting
confidence: 59%
See 1 more Smart Citation
“…We also demonstrated that low DUSP3 levels had a significant correlation with high KDM2A levels and often occurred in NSCLC tumors. In line with our results, it has been shown that DUSP3 is downregulated in NSCLC and that DUSP3 overexpression leads to decreased cell proliferation and reduced tumor growth in a xenograft mouse model (24). Together with this Stably KDM2A-depleted (shKDM2A#1 and shKDM2A#2) cells and control cells (shControl) were subcutaneously implanted into mice.…”
Section: Tablesupporting
confidence: 59%
“…DUSP3 has been shown to suppress the activities of ERK1/2 and JNK1/2 in HeLa cells and the activity of EGFR in the lung cancer cell line H1299 by dephosphorylating these kinases (22)(23)(24)(25). ERK1/2 and JNK1/2 are a family of MAPKs that play a critical role in mediating cellular signaling events, including cell proliferation and invasion (26)(27)(28)(29).…”
Section: Figurementioning
confidence: 99%
“…Increased ErbB tyrosine kinase activity drives several cancer-relevant properties including proliferation, cell motility, and invasion [36]. dusp3 over-expression removed the activating phosphate from Y992 of ErbB, preventing ErbB kinase activity [33]. As the ErbB family of proto-oncogenes is strongly associated with cancers in a kinase dependent manner [37], the ability of DUSP3 to inhibit its activity may have important implications for cancer therapies.…”
Section: Dusp3/vhrmentioning
confidence: 99%
“…Nevertheless, as a functional MAPK phosphatase, it is not surprising that DUSP3 is implicated in cancer, where it has been alternatively described as having both oncogenic [30][31][32] and tumor suppressive [33,34] properties.…”
Section: Dusp3/vhrmentioning
confidence: 99%
“…This raises the question whether dephosphorylation of the MAPKs by VHR in vivo is aided by any recruiting strategy. Other than the MAPKs, signal transducers and activators of transcription 5 (STAT5) with a single Tyr(P) site, epidermal growth factor receptor, and ErbB2 have also been reported as VHR substrates (18,19). Two recent studies showed that phosphorylation of VHR at Tyr 138 is required for its efficient dephosphorylation of MAPKs and STAT5 in vivo (18,20).…”
mentioning
confidence: 99%